Human MAIT cells respond to and suppress HIV-1 - Phetsouphanh, C; Phalora, P; Hackstein, C-P; Thornhill, J; Munier, CML; Meyerowitz, J; Murray, L; VanVuuren, C; Goedhals, D; Drexhage, L; Moore, R; Sattentau, QJ; et al. (eLife Sciences Publications, 2021)
Human MAIT cells sit at the interface between innate and adaptive immunity, are polyfunctional and are capable of killing pathogen infected cells via recognition of the Class IB molecule MR1. MAIT cells have recently been shown to possess an antiviral protective role in vivo and we therefore sought to explore this in relation to HIV-1 infection. There was marked activation of MAIT cells in vivo in HIV-1-infected individuals, which decreased following ART. Stimulation of THP1 monocytes with R5 tropic HIVBAL potently activated MAIT cells in vitro. This activation was dependent on IL-12 and IL-18 but was independent of the TCR. Upon activation, MAIT cells were able to upregulate granzyme B, IFNγ and HIV-1 restriction factors CCL3, 4, and 5. Restriction factors produced by MAIT cells inhibited HIV-1 infection of primary PBMCs and immortalized target cells in vitro. These data reveal MAIT cells to be an additional T cell population responding to HIV-1, with a potentially important role in controlling viral replication at mucosal sites.